(untitled) (Eurasian Medical Research Periodical, 2026)
Inflammatory diseases of the mucous membranes of the nasal cavity and paranasal sinuses remain one of the most common pathologies within the spectrum of ENT disorders; among these, lesions of the maxillary sinuses constitute the largest proportion of sinusitis cases. Their high prevalence, tendency toward a chronic and recurrent course, as well as the limited efficacy of traditional treatment methods, underscore the necessity of refining surgical approaches. The aim of this study was to optimize the surgical management of patients with chronic inflammatory diseases of the maxillary sinuses through the implementation of a minimally invasive endoscopic technique. The study involved 101 patients (45 women and 56 men) aged 15 to 75 years. Maxillary sinus cysts were diagnosed in 37 patients; fungal lesions (mycetomas) in 16; polyposis in 37; and chronic purulent sinusitis in 11 patients. All patients underwent an endoscopic procedure performed via a mini-access approach using a Kozlov trocar. The developed technique enabled comprehensive visualization of all compartments of the sinus and the radical removal of pathological formations (cysts, polyps, fungal masses, and foreign bodies) under endoscopic guidance, while ensuring minimal tissue trauma. The application of minimally invasive surgical principles contributed to reduced rehabilitation times and a lower risk of postoperative complications